A woman with forearm amyotrophy - Sagui, Emmanuel (BMJ Publishing Group, 2009)
We present the case of a 33-year-old woman with benign sporadic monomelic amyotrophy of the distal part of the arm, called Hirayama disease. Clinical features included forearm amyotrophy sparing the brachioradialis muscle, cold paresis and causalgia. Neck magnetic resonance imaging was normal in neutral and flexion position. Electromyography showed denervated patterns in the extensor digitorum communis, and conduction studies ruled out multifocal motor neuropathy. Motor evoked potentials were normal. Serum IgG anti-GM1 antibodies were moderately raised but were negative 8 months later. Outcome was favourable within 15 months, with partial motor recovery. Pathogenesis remains controversial: neck flexion induced myelopathy via chronic anterior horn ischaemia due to forward displacement of the posterior wall of the dura mater, or benign variant of lower motor neuron disease? Whatever the pathomechanism is, the clinical features and outcome are the same.